Uji Daya Terima dan Analisis Kandungan Zat Gizi Keripik Bawang Substitusi Tepung Cangkang Telur Sebagai Alternatif Pangan Sumber Kalsium - Lusi Anindia Rahmawati; Zakia Umami; Dewi Elfidasari; Annisa Sabrina Sekar Langit (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2024)
Eggshells are part of urban wastes. The nutrition content in eggshells is 94% calcium carbonate, 1% potassium phosphate, and 1% magnesium carbonate. One alternative to overcome this waste is to utilize it as eggshell flour. This study aims to determine the acceptability, analyse the nutritional content, and assess the contribution of nutrients to the Reference Nutrition Label (ALG) of onion chips substituted with eggshell flour as an alternative food source of calcium. This type of research is experimental with a completely randomized design. The eggshell flour used was commercial and non-commercial eggshell flour with a total of eight (8) formulas. Panelists were 30 students of University Al-Azhar Indonesia with two replicates. The results of the organoleptic test (hedonic and hedonic quality) were analyzed using the Kruskal-Wallis test, with the Mann-Whitney further test at a real level of 5%. The results showed that the A1B1 formula with the addition of eggshell flour as much as 10% and the use of commercial eggshell flour as the selected formula based on the Exponential Comparison Method (MPE). The results of the analysis of the nutritional content of the selected formula per 100 grams are energy 505 kcal, protein 9 grams, fat 31,5 grams, carbohydrates 46 grams, water content 4,3 grams, ash content 9,5 grams, and calcium 414,8 mg. Based on the nutrient contribution analysis, the product contributed 15,1% of calcium.Keywords – Eggshell, Onion Crisps, Substitution, Nutrient Content, Calcium